Emotions towards magnetic resonance imaging in people with multiple sclerosis. (28th March 2019) - Engels, Katharina; Schiffmann, Insa; Weierstall, Roland; Rahn, Anne Christin; Daubmann, Anne; Pust, Gesa; Chard, Declan; Lukas, Carsten; Scheiderbauer, Jutta; Stellmann, Jan‐Patrick; Heesen, Christoph
Abstract : Objectives: People with multiple sclerosis (pwMS) often have magnetic resonance imaging (MRI) examinations. While MRI can help guide MS management, it may be a source of anxiety for pwMS. We aimed to develop and validate a questionnaire on the "EMotions and Attitudes towards MRI" (MRI‐EMA). Material and Methods: The questionnaire was developed, tested in two samples of pwMS and validated in a sample of n = 457 pwMS using exploratory (EFA) and confirmatory factor analysis (CFA). Results: EFA revealed four factors underlying the questionnaire: fear of MRI scan, fear of MRI results, feeling of control over the disease and feeling of competence in the patient‐physician encounter . CFA confirmed the model fit. Receiving the MRI results, but not undergoing the procedure was associated with anxiety. Seeing MRI results gave participants a feeling of control over the disease. Only 50% felt competent to discuss MRI findings with their physician. Fear of MRI results was especially high and feeling of competence low in participants with a short disease duration and little MRI experience. Conclusion: PwMS do not feel competent when discussing the role, MRI plays in their care. Receiving MRI results caused anxiety and provides some pwMS with a—perhaps false—feeling of control over the disease. The MRI‐EMA constitutes a new tool for the assessments of pwMS' feelings towards MRI, that can be applied in future research and clinical settings.